The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1049/cmu2.12372
|View full text |Cite
|
Sign up to set email alerts
|

Secrecy‐oriented user association in ultra dense heterogeneous networks against strategically colluding adversaries

Abstract: Network densification is recognized as the key technology to meet the ever growing demand of data traffic in next generation wireless networks. However the proliferation of small cell base stations (SCBSs) introduces vulnerabilities to information security, as they are prone to eavesdropping attacks. In this paper, it is studied how user association strategies can be specifically tailored to meet this security challenge in a ultra dense heterogeneous cellular network(UDHCN) with a group of colluding eavesdropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Through simulations, they demonstrated that their approach outperforms orthogonal frequency domain multiplexing (OFDM) based transmission benchmarks. Finally, the authors in [102] investigated user association strategies to address security issues in an ultra-dense HetNet with a group of colluding eavesdroppers. A zero-sum game was proposed to reflect the conflicting objectives of users and eavesdroppers.…”
Section: Eve-exclusion Zone + An Designmentioning
confidence: 99%
“…Through simulations, they demonstrated that their approach outperforms orthogonal frequency domain multiplexing (OFDM) based transmission benchmarks. Finally, the authors in [102] investigated user association strategies to address security issues in an ultra-dense HetNet with a group of colluding eavesdroppers. A zero-sum game was proposed to reflect the conflicting objectives of users and eavesdroppers.…”
Section: Eve-exclusion Zone + An Designmentioning
confidence: 99%
“…Through simulations, they demonstrated that their approach outperforms orthogonal frequency domain multiplexing (OFDM) based transmission benchmarks. Finally, the authors in [105] investigated user association strategies to address security issues in an ultra-dense HetNet with a group of colluding eavesdroppers. A zero-sum game was proposed to reflect the conflicting objectives of users and eavesdroppers.…”
Section: ) Cognitive Radio Networkmentioning
confidence: 99%
“…HetNet has various different topologies, such as spectrum resource allocation in HetNets can allocate resources intelligently based on network topology, user location, and demand, and has wide applicability in practical applications. For instance, intelligent matching theory is used in [8] to address user access problems in ultra-dense HetNets to boost energy efficiency. Dual decomposition is employed in [9] to allocate small cell frequencies in heterogeneous ultradense networks to improve spectrum efficiency.…”
Section: Udn Resource Allocation Application Scenariosmentioning
confidence: 99%